Mitochondrial protein adduct and superoxide generation are prerequisites for early activation of c-jun N-terminal kinase within the cytosol after an acetaminophen overdose in mice. (1st March 2021) - Nguyen, Nga T.; Du, Kuo; Akakpo, Jephte Y.; Umbaugh, David S.; Jaeschke, Hartmut; Ramachandran, Anup
Graphical abstract: Highlights: Early APAP-induced mitochondrial protein adduct formation precedes JNK activation. Mitochondrial-derived free radicals in cytosol required for initial JNK activation. Spatially directed mitochondrial superoxide release activates cytosolic JNK. Abstract: Acetaminophen (APAP) overdose is the most common cause of acute liver failure in the United States and formation of APAP-protein adducts, mitochondrial oxidant stress and activation of the mitogen activated protein (MAP) kinase c-jun N-terminal kinase (JNK) are critical for APAP-induced cell death. However, direct evidence linking these mechanistic features are lacking and were investigated by examining the early temporal course of these changes in mice after 300 mg/kg APAP. Protein adducts were detectable in the liver (0.05−0.1 nmol/mg protein) by 15 and 30 min after APAP, which increased (>500 %) selectively in mitochondria by 60 min. Cytosolic JNK activation was only evident at 60 min, and was significantly attenuated by scavenging superoxide specifically in the cytosol by TEMPO treatment. Treatment of mouse hepatocytes with APAP revealed mitochondrial superoxide generation within 15 min, accompanied by hydrogen peroxide production without change in mitochondrial respiratory function. The oxidant stress preceded JNK activation and its mitochondrial translocation. Inhibitor studies identified the putative source of mitochondrial superoxide as complex III, which released superoxide towards the intermembrane space after APAP resulting in activation of JNK in the cytosol. Our studies provide direct evidence of mechanisms involved in mitochondrial superoxide generation after NAPQI-adduct formation and its activation of the MAP kinase cascade in the cytosol, which are critical features of APAP hepatotoxicity.